Health supplement products use among patients with chronic illnesses: A multicenter study in rural areas of Sarawak, Malaysia - Shing Chyi Loo, Chee Ping Chong, Chuo Yew Ting, Meng Hsiung Tan, Luqman Nulhakim Said (Journal of Applied Pharmaceutical Science, 2020)
Health supplement products (HSPs) are gaining public acceptance in Malaysia. However, little is known about the practices and perceptions of HSPs among patients in rural areas. This study aims to explore the prevalence of concomitant use of HSPs with prescribed medicine, practices, perceptions, and factors influencing the consumption of HSPs among patients with chronic illnesses in rural areas of Sarawak, Malaysia. A multicenter cross-sectional study was conducted in the outpatient pharmacy department of seven districts’ hospitals from June to August 2018. A data collection form and questionnaire were developed and pilot tested prior to the data collection. Bivariate logistic regression was used to assess the association between patients’ sociodemographic characteristics and the use of HSPs. A total of 350 patients participated in the study. Only 84 (24.0%) patients were active HSP users and 54 (64.3%) of them always used HSPs concomitantly with prescribed medicines. Approximately half (52.0%) of the patients never consult healthcare providers about the use of HSPs. However, the majority of them expressed agreement upon the necessity to consult healthcare providers prior to HSP use (82.0%) or during the concomitant use of HSPs with prescribed medicines (80.3%). Patients with monthly household incomes of more than RM 2000 (USD 480.59) (n = 84) were 4.23 times significantly (p < 0.001) more likely to consume HSPs than those with an income of RM 830 (USD 199.44) or less (n = 173). In conclusion, the concomitantly used HSPs with prescribed medicines is prevalent among patients and educational interventions are needed to enhance the safe use of such products.
Keywords: Health supplement product, prevalence, practice, perception, factor, rural area.